Al-nashāṭ al-lāṣfī al-raqmī li-mutaʿallimī al-lughah al-ʿArabīyah al-mustawá al-thānī al-Indūnīsiyyīn: Anwāʿuhu wa fawaiduhu - Rita Febrianta; Mohamed Daud Mohamed (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
The title of this article is the digital extracurricular activity of the Indonesian level two-Arabic language learners: its types and benefits. Aims of this article are to define the digital virtual extracurricular activity, explain what is related to it, reveal the difficulties that learners face in it, and stay within its limits the digital extra-curricular activities via WhatsApp for Indonesian Arabic language learners at the Manarat Center of Southeast Asia. I relied on the foundations of the descriptive approach. The research consists of an introduction, the definition of the digital extracurricular activity and a reflection of the practical experience in implementing the digital extracurricular activity, an analysis of the linguistically practiced activity, an indication of its type, objectives and benefits, then an inventory of technical obstacles and difficulties in it. The article concludes with more than two numeric activities, which are the most prominent of them. One of the types of digital activity in another aspect, the digital extracurricular activity helps in acquiring Arabic as a foreign language and enhances its four skills. It has enabled Indonesian learners to provide various materials that help them to select the most important ideas, sound expressions and correct methods. Broadcasted via different channels and medias.